2002
DOI: 10.1128/jb.184.10.2699-2708.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Quorum-Sensing Signaling System Essential for Genetic Competence in Streptococcus mutans Is Involved in Biofilm Formation

Abstract: In a previous study, a quorum-sensing signaling system essential for genetic competence in Streptococcus mutans was identified, characterized, and found to function optimally in biofilms (Li et al., J. Bacteriol. 183:897-908, 2001). Here, we demonstrate that this system also plays a role in the ability of S. mutans to initiate biofilm formation. To test this hypothesis, S. mutans wild-type strain NG8 and its knockout mutants defective in comC, comD, comE, and comX, as well as a comCDE deletion mutant, were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
409
3
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(440 citation statements)
references
References 45 publications
15
409
3
4
Order By: Relevance
“…Thus, our results demonstrated that supplementation with the DD2 culture supernatant could influence fructan production in S. mutans . Furthermore, the downregulation of ftf was accompanied by decreases in the expression levels of comDE and brpA (Figure 4), which are also involved in the biofilm formation and play a critical role in the regulation of stress responses [9,37]. Interestingly, the expression level of vicR (Figure 4) – which encodes proteins that regulate the expression of virulence factors involved in polysaccharide synthesis and those that integrate external signals in a regulatory network composed of ftf, gtfB , and gtfC [37] – was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our results demonstrated that supplementation with the DD2 culture supernatant could influence fructan production in S. mutans . Furthermore, the downregulation of ftf was accompanied by decreases in the expression levels of comDE and brpA (Figure 4), which are also involved in the biofilm formation and play a critical role in the regulation of stress responses [9,37]. Interestingly, the expression level of vicR (Figure 4) – which encodes proteins that regulate the expression of virulence factors involved in polysaccharide synthesis and those that integrate external signals in a regulatory network composed of ftf, gtfB , and gtfC [37] – was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococci are also known to aggregate to form oral biofilms; for instance, S. mutans rapidly increases biofilm thickness by producing surface-associated and biofilm regulatory proteins [7,9,10]. As such, reducing the size of cariogenic bacterial populations and suppressing biofilm formation are essential strategies for the prevention of oral diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…The VicRKX and LiaFSR two-component signal transduction systems (TCSTS) have been reported as the master regulatory system involved in expression of GTFs, biofilm formation and environment stress tolerance in S. mutans [8,9]. The ComCDE system quorum sensing (QS) system enables intra-species cell–cell communication [10]. As these TCSTS are selective for the bacteria and not the host, they are regarded as excellent therapeutic targets for antimicrobial agents [11].…”
Section: Introductionmentioning
confidence: 99%
“…The QS system typical of streptococci is regulated by a peptide pheromone signal called competence stimulating peptide (CSP) [9], which is species-specific and detected by a histidine-kinase [10]. The inactivation of any of the genes related to the CSP QS system results in the alteration of biofilm architecture [11]. The other QS signal related to biofilm formation in S. mutans is AI-2 [7,12,13], which has been proposed as a universal signalling molecule due to its wide distribution among prokaryotes [14,15], including important oral pathogens [16].…”
Section: Introductionmentioning
confidence: 99%